ANALYSIS OF DEVELOPMENT OPTIONS FOR GENERATING CAPACITY IN THE REPUBLIC OF MOLDOVA - Zaitsev D.A.; Golub I.V.; Kalinin L.P.; Tirshu M. (Problems of the Regional Energetics)
The paperwork deals with analysis of scenario concerning integration of Moldova’s right bank power system to ENTSO-E. In the paperwork are proposed and analyzed different variants of generation capacity development on the territory of republic’s right bank considering tasks mentioned in the Energy Strategy of Republic Moldova by 2030. For every proposed variant of generation capacity development the analysis of normal modes regarding active power losses was performed for both in whole power system and separately in every of their elements with differentiation by voltage levels. There were performed the computation and estimation of coefficients of static stability reserve by active power and by voltage and also were estimated the import/export of electrical energy as well as were analyzed many other modes of indicators. As result of comparative analysis, the more technical effective variants (in author’s opinion) were selected.